2021
DOI: 10.1515/secm-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic textile biocomposites: Using laboratory testing and digital fabrication to develop flexible living building materials

Abstract: Urban development and the construction industry account for a considerable proportion of global carbon dioxide (CO2) emissions. Emerging biological materials, such as those proposed in this paper, seek to utilize the metabolic functions of living microorganisms to reduce some of the negative impacts of humans on the environment. The material explorations demonstrated in this paper propose a living photosynthetic carbon capture textile for the built environment. We demonstrate making practices that integrate li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this regard, they tested an array of flexible, textile-based microalgae bio-composites that could be integrated into the internal fabric of the built environment (Figure 5C). Generally, they compared four textile types (cotton, hessian, polyester, and canvas) and a range of matrices that contain living algae and demonstrated that microalgae (chlorella vulgaris) can be cultivated in a minimal moisture environment in a range of matrices and on a variety of textiles that lend themselves to a range of potential applications within the building fabric [42]. textile material and demonstrated that a green species of microalgae can be cultivated in a moisture environment in a range of matrices and on a variety of textiles that can have different applications.…”
Section: Case Study 3: Algae-based Hygromorphic Actuatormentioning
confidence: 99%
“…In this regard, they tested an array of flexible, textile-based microalgae bio-composites that could be integrated into the internal fabric of the built environment (Figure 5C). Generally, they compared four textile types (cotton, hessian, polyester, and canvas) and a range of matrices that contain living algae and demonstrated that microalgae (chlorella vulgaris) can be cultivated in a minimal moisture environment in a range of matrices and on a variety of textiles that lend themselves to a range of potential applications within the building fabric [42]. textile material and demonstrated that a green species of microalgae can be cultivated in a moisture environment in a range of matrices and on a variety of textiles that can have different applications.…”
Section: Case Study 3: Algae-based Hygromorphic Actuatormentioning
confidence: 99%
“…To create the foundation of the bio-gel matrix, at room temperature, kappa-carrageenan (from >99.9% pure powder) has been added to a dilution series of BG11 (Blue-Green medium with the full strength of 75%, 50%, and 25% dilution) and mixed[ 131 ].…”
Section: Application Of Bioinks For Printing Algal Cellsmentioning
confidence: 99%
“…After achieving a gel-like consistency, C. vulgaris was added to the solution, which is then mixed until it was completely homogenous, after which Aloe Vera was added. For chitosan treatments, chitosan powder (food grade) has been dissolved in a dilution series of BG11 after the addition of acetic acid (0.3 mL/10 mL) to the solution[ 131 ]. Once the final solution is gel-like in consistency and all components are homogenous, printing can begin.…”
Section: Application Of Bioinks For Printing Algal Cellsmentioning
confidence: 99%
See 1 more Smart Citation